The Review of Potential Application of Recycled Glass Powder as Partial Replacement of Sand in Concrete - Mhd Shabri, Nur Afifah; Hamdan, Rafidah (Recent Trends in Civil Engineering and Built Environment, 2024)
The growth production and manufactured sector in Malaysia had led to increasing the industrial by-product waste, especially glass. Every year, millions of tonnes of glass waste are produced around the world. Glass is disposed of as waste in landfills, which is unsustainable because it does not disintegrate into the environment. These growing problems of glass waste can be reduced if a new disposal method is utilized other than disposed of it to the landfill. This study is focused on the utilization of glass waste with sand replacement. The main objectives of this study are to determine the characteristics of glass waste and to conduct physical and mechanical properties tests towards the concrete with different percentages of glass as an example (10%, 20%, and 30%). Concrete is one of the most often utilized building materials in the world. Concrete mixing ratios necessitate sand, and the quantity of sand is diminishing as a result of increased economic consumption, and sand dredging can be hazardous to the environment. It’s possible that this will lead to calamity for us in the future. Environmental concerns are a major factor in the building and concrete industry’s long-term viability.